You are a badass at making money : master the mindset of wealth / Jen Sincero. - Sincero, Jen, 1965-
A refreshingly frank and entertaining guide for anyone who's ready to start raking in the dough. Drawing on her own experience of transforming herself--over just a few years--from a woman living in a converted garage with tumbleweeds blowing through her empty bank account to a woman who travels the world in style, Sincero knows all of the BS you can get wrapped up in when it comes to money, as well as what it takes